If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2n + -3) = 2n + -2(n + -1) Reorder the terms: 2(-3 + 2n) = 2n + -2(n + -1) (-3 * 2 + 2n * 2) = 2n + -2(n + -1) (-6 + 4n) = 2n + -2(n + -1) Reorder the terms: -6 + 4n = 2n + -2(-1 + n) -6 + 4n = 2n + (-1 * -2 + n * -2) -6 + 4n = 2n + (2 + -2n) Reorder the terms: -6 + 4n = 2 + 2n + -2n Combine like terms: 2n + -2n = 0 -6 + 4n = 2 + 0 -6 + 4n = 2 Solving -6 + 4n = 2 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4n = 2 + 6 Combine like terms: -6 + 6 = 0 0 + 4n = 2 + 6 4n = 2 + 6 Combine like terms: 2 + 6 = 8 4n = 8 Divide each side by '4'. n = 2 Simplifying n = 2
| m=4+m | | -5(-2x+3)= | | 7x-3y+9x-2y= | | Dx+9y=27 | | 5/8(x-7)=10 | | logv[12](x)+logv[12](11x-1)=1 | | 12x+5y=8400 | | 12x=6x+20-8 | | 5p+7s+4p-3s= | | 4x-32=9x+17 | | 15m^2-5m^2=30m+11m | | 7x+4y+2x-6y= | | 3x+7=5x-q | | 5x+12y=8400 | | 27=9s | | 10x-5=8x+15 | | (2x-3)/(5-3x)0 | | =(x+y-1)+(x+y+1)-(x+y-z) | | 4b-9b= | | 3x-20=x+8 | | 9+35r+25r=35r+34r | | x=3x^2+2x+6 | | F+2f+4f= | | x^2+y^2-10x+9y+1=0 | | 81/:5/6 | | 5p+3p+4p= | | x^2y^2-10x+9y+1=0 | | -16-(-38)=x/5 | | log(3)+log(2)= | | y[(x^3)(y^3)+(2x^2)-(y)]dx+[(x^4)(y^3)-(2x^3)]dy=0 | | k=3r-8 | | y(x^3y^3+2x^2-y)dx+(x^4y^3-2x^3)dy=0 |